PENERJEMAHAN HARFIAH: DOMINASI DALAM TEKNIK PENERJEMAHAN SURAT INFORMAL - Arif Hidayat (Wanastra: Jurnal Bahasa dan Sastra, 2020)
Translation techniques are expected to be solutions to cope with translation problems faced by translators. Due to this reason, translation learners are taught these techniques to be their provision in handling translation problems they will face as professional translators. This research is aimed at giving comprehension of the using translation techniques tendency in informal letter translation. Case study method is used in this research to analyze how English Letters students who have learnt translation through qualitative approach and document data collecting technique. This research uses Molina & Albir's (2002)Translation Techniques to identify the translation technniques used by the students.The result shows that the dominance of literal translation technique by a very significant data finding from the eleven techniques used with normal distribution ranging from 17 until 27 data per students.In the next research, it is hoped that there will be wider scope of study to analyze the trends of translation techniques in those students’ affiliation.Keywords: Literal Translation, Teknik Penerjemahan, Informal Letter